Terahertz-Based Joint Communication and Sensing for Precision Agriculture: A 6G Use-Case - Usman, Muhammad; Ansari, Shuja; Taha, Ahmad; Zahid, Adnan; Abbasi, Qammer H.; Imran, Muhammad Ali (Frontiers in Communications and Networks, 2022)
By 2050, experts estimate that the agricultural produce must increase by 60% to 70% to meet the needs of the ever increasing population of the world. To this aim, the concept of precision agriculture or smart farming has recently been coined. The idea of precision agriculture is well represented as a smart management system, having the ability to monitor, observe, sense, measure and control the health and water contents in plants at nano-scale and crops at macro-scale. The goal is to maximise the production while preserving the vital resources. The combination of terahertz (THz) based sensing technology to estimate plant health at a cellular level, and wireless sensor networks deployed within crops to monitor different variables while making intelligent decisions is far reaching. The integration and operation of such a macro-nano-sensor system requires a sustainable communication infrastructure that considers the demands of remote and agile agricultural environments. In this paper, an integrated sensing and communication system for plant health monitoring that utilises THz signals, is presented as a 6G use case. The joint architecture is outlined and various challenges including energy harvesting, practical implementation among others, followed by recommendations for future research are presented.